A facile synthesis of metal ferrites (MFe2O4, M = Co, Ni, Zn, Cu) as effective electrocatalysts toward electrochemical hydrogen evolution reaction. (29th May 2022) - Belhadj, Hamza; Messaoudi, Yazid; Khelladi, Mohamed R.; Azizi, Amor
Abstract: Developing low-cost, stable, and robust electrocatalysts for hydrogen evolution reaction (HER) is highly desirable for large-scale application. In this study, a highly efficient electrocatalysts of metal ferrites (MFe2 O4, M = Co, Ni, Zn, Cu) with superior activity and durability are successfully fabricated on copper substrate through a facile co-precipitation method followed by doctor-blading deposition. The electrocatalytic performance of CoFe2 O4, NiFe2 O4, ZnFe2 O4 and CuFe2 O4 electrodes for hydrogen evolution reaction is studied in alkaline media using polarization curves and electrochemical impedance spectroscopy (EIS). Among them, CoFe2 O4 presented the best electrocatalytic activities for HER with extremely low overpotentials of 270 mV (vs. RHE) at a current density of 10 mA cm −2 in 1 M KOH. The electrocatalytic activity of MFe2 O4 (M = Co, Ni, Zn, Cu) for HER to generate current density of 10 mA cm −2 with low overpotential followed the order of CoFe2 O4  > CuFe2 O4  > NiFe2 O4  > ZnFe2 O4 . The highly improved HER performance of CoFe2 O4 is mainly due to a large number of exposed active sites, high electrical conductivity and low apparent activation energy, which are confirmed by a remarkable electrochemically active surface area (ECSA = 53.17 cm 2 ), Nyquist plots analysis and Arrhenius plots measurement, respectively. Moreover, the CoFe2 O4 electrode showed outstanding electrocatalytic stability even after 1000 cyclic voltametry tests. These results provide a promising avenue for developing cost-effective and high-efficiency electrocatalysts based on earth-abundant transition metal ferrite as advanced electrodes for large-scale energy conversion processes. Graphical abstract: Image 1 Highlights: MFe2 O4 (M = Co, Ni, Zn, Cu) electrodes are prepared using a facile co-precipitation method. The prepared CoFe2 O4 electrode exhibits a promising electrocatalytic activity towards HER. The performance of MFe2 O4 toward HER was favored by high ECSA, and low Ea values. CoFe2 O4 follows Volmer-Heyrovsky mechanism with excellent long-term durability in 1 M KOH.